2020
DOI: 10.1177/2150132720935296
|View full text |Cite
|
Sign up to set email alerts
|

Review of Web-Based Toolkits for Health Care Practitioners Working With Women and Girls Affected by or at Risk of Female Genital Mutilation/Cutting

Abstract: Increased migration has given rise to more advocacy efforts against female genital mutilation or cutting (FGM/C), legislation that criminalizes the practice, and guidance to the health sector for managing care of affected groups. More women and girls who have been cut or who are at risk of FGM/C are migrating from regions where it is common to countries where it is not and interacting with health professionals and other community practitioners in these host countries. Despite numerous studies on the negative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…There is evidence that mLearning interventions, such as smartphone applications or web-based toolkits, are cost-efficient and can increase providers’ knowledge and skills [ 15 ]. A 2020 review identified 31 web-based toolkits with information about FGM/C and medical treatment recommendations targeting healthcare providers [ 16 ]. There exists one mLearning FGM/C application for healthcare providers in the United Kingdom [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that mLearning interventions, such as smartphone applications or web-based toolkits, are cost-efficient and can increase providers’ knowledge and skills [ 15 ]. A 2020 review identified 31 web-based toolkits with information about FGM/C and medical treatment recommendations targeting healthcare providers [ 16 ]. There exists one mLearning FGM/C application for healthcare providers in the United Kingdom [ 17 ].…”
Section: Introductionmentioning
confidence: 99%